Formulasi Gel Transfersom Limbah Kulit Bawang Merah (Allium cepa. L) menggunakan Perbandingan Fosfolipid dan Surfaktan - Winda Permata Sari; Soniya Tamara; Sherli Permatasari; Septia Andini (JURNAL ILMU KEFARMASIAN INDONESIA, 2020)
Red onion tunic waste contains quercetin which has anti-inflammatory activity. The formulation of anti-inflammatory preparations with the transdermal route is a solution towards the effect of gastrointestinal in the oral route. Transfersome is a nano vesicle particle that can increase the penetration of transdermal formulation. This study aims to characterize red onion tunic waste transfersome based on the ratio of phospholipids and surfactants used. The formulation of the best transfersome will be made into gel based formulation and the particle will be evaluated. Transfersome is made in 3 formulas namely Formula 1 (F1) with a ratio of phospolipids:surfactant (90:10), F2 (85:15), and F3 (70:30). This characterization included particle size distribution, potential zeta, entraptment efficiency, deformability index, and vesicle morphology. The best transfersome formulas are then formulated into gel preparations. The results showed that the best transfersome formula was F1 (90:10), with an average particle size of 357.9 ± 6.3 nm, zeta potential of -24.9 ± 0.9 and the entraptment efficiency results reached 77.964%. The morphology of the vesicles produced is spherical according to the expected vesicle criteria, but in gel-based formulation, the particle size not distributed homogenously.